Analisis Daya Dukung Tanah Workshop Km 25 Berdasarkan Data Sondir Di PT KPP Site Asto, Kalimantan Tengah - Alfandias Seysna Putra; Isdaryanto Iskandar (Prosiding Sains dan Teknologi, 2022)
The planning of the substructure of the building cannot be separated from the process of soil investigation to determine the bearing capacity of the soil to be supported by the building. The location of the mining area, especially in Central Kalimantan, is dominated by a layer of sand, so it is necessary to investigate the soil first to obtain the depth of the soil layer in the form of very dense sand with a qc of 155 – 250 kg/cm2. The purpose of this study was to determine the characteristics of the soil layer and the carrying capacity of the soil in the construction area of the KM 25 Workshop. The method used in this study was a literature study method and in-situ testing. Based on the test results from 6 test points, it was found that the soil layer at the research site was dominated by a layer of sand with a surface layer at a depth of 0.20 – 1.60 meters in the form of cohesive soil of very soft to soft consistency. Hard soil layers were found from 7.00 – 8.20 meters depth with a qc of 155 – 250 kg/cm2. Keywords: Sondir Test, Soil Bearing Capacity, Substructure, Dutch Cone Penetrometer Test